PENYULUHAN PENYAKIT HIPERTENSI DAN DIABETES MELLITUS PADA LANSIA DAN PENGENALAN TERAPI KOMPLEMENTER UNTUK MANAJEMEN NYERI - Agung Nugroho, Fajar; Irmawan Andri , Nugroho; Maura Ros , Valentina; Fajar Agung, Nugroho (Aspirasi Masyarakat, 2025)
Diabetes also increases the risk of hypertension. Chronically elevated blood glucose levels in individuals with diabetes can damage blood vessels, causing them to become stiff and narrowed, which ultimately raises blood pressure. Chronic pain in the elderly not only reduces their quality of life but also limits daily activities and may worsen underlying medical conditions. Many elderly individuals lack adequate knowledge about non-pharmacological or complementary methods of pain management, often relying solely on painkillers, which carry the risk of side effects when used long-term. The purpose of this devotion to improve the knowledge of elderly individuals with hypertension and diabetes mellitus regarding the management of their conditions and to introduce various safe and effective complementary therapies to reduce pain among those with diabetes and hypertension at the Integrated Health Coaching Post (Posbindu) in Gunung Mujil Village, Gombong Subdistrict. This activity included a health education session on chronic diseases (diabetes mellitus and hypertension) combined with a pre-test and post-test, as well as a demonstration of autogenic complementary therapy. A total of 54 participants with diabetes mellitus and hypertension attended, with educational backgrounds ranging from elementary school (10%), junior high school (20%), and high school (70%). The average participant knowledge scores across all question categories (pre-test and post-test) showed a significant increase from the pre-test to the post-test phase. The overall average knowledge score increased dramatically from 43.6 points to 87.2 points, indicating nearly a twofold improvement following the health education intervention.